Apprenticeship non‑completion in Germany: a money matter? - Neuber‑Pohl, Caroline [Verfasser] (My University, 2021)
“German establishments heavily rely on the apprenticeship system for skill supply. With one in four apprenticeship contracts ending before successful completion, it is in the interest of establishments and policy-makers to determine factors, which reduce non-completion. This paper investigates the role of apprenticeship wages and income prospects after completion for apprenticeship non-completion in Germany. For this purpose, this study identifies incidences of apprenticeship non-completion in a large sample of administrative data on employment biographies and estimates a piecewise exponential model of the non-completion hazard with shared frailties by occupations. The results suggest a robust and significant association with both apprenticeship wages and skilled worker wages. All else at means, apprenticeships which are paid 5% more than the mean apprenticeship wage, on average have a 0.8 percentage points higher estimated survival rate. In turn, an apprenticeship expected to lead to a skilled job that is paid 5% above average, has an estimated survival rate, which is 3.1 percentage points higher on average. These findings highlight the importance of income prospects for apprenticeship non-completion.” (author’s abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); 370; 330; Berufsausbildung; Ausbildungsverlauf; Ausbildungsabbruch; Ausbildungswechsel; Einflussfaktor; Ausbildungsvergütung; Lohnhöhe; Quantitative Angaben